Enhancing perovskite solar cell performance: The role of polymer-assisted hole transport layers in hot carrier dynamics - Xu, Min; Wang, Peng; Qi, Shuwen; Zhao, Rongjun; Xie, Lin; Hua, Yong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•This work reveals that incorporating a polymer material (P(NDI2OD-T2)) into hole transport layer (HTL) can efficiently enhance PSCs efficiency and stability.•We found that improving extraction and transfer of hot carriers from perovskite layer to HTL is favorable for reducing the recombination of charge carriers in the device.•The findings of the present work can provide a deep understanding of the photoinduced carrier dynamics towards develop high-performance devices based on additives. Enhancing the efficiency and stability is very critical for perovskite solar cells (PSCs) commercialization. Herein, we report an effective approach to enable highly efficient and stable PSCs by incorporating a polymer material, poly[N, N′-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5′-(2,2′-bithiophene) (named P(NDI2OD-T2)), into hole transport layer (HTL). Our research results exhibit that the addition of P(NDI2OD-T2) not only effectively improves the hole mobility and conductivity of HTL, but also makes its energy level more alignment with perovskite. More importantly, ultrafast carrier results demonstrate that the introduction of P(NDI2OD-T2) into Spiro-OMeTAD HTL can effectively improve the extraction and transfer of hot carriers from perovskite layer to HTL, and consequently reduce the recombination of charge carriers in the device. As a result, PSCs based on Spiro + P(NDI2OD-T2) as a HTL shows an enhanced power conversion efficiency (PCE) of 24.20 %, which is much higher than that of control device without P(NDI2OD-T2) (21.94 %). Furthermore, the un-encapsulated P(NDI2OD-T2)-treated PSCs exhibit excellent humidity, thermal and light stabilities, with the devices maintaining 94 % of its initial efficiency after 3000 h at ≈40 % humidity, 95 % of its initial efficiency after storage at 65 °C and 85 °C for 600 h, and 90 % of its initial efficiency after 600 h under one sun light irradiation, respectively. This work provides an effective strategy for improving the device efficiency and long-term stability of PSCs.